The 12th century bronze doors of Barisanus of Trani in Trani, Ravello and Monreale - Marianne Mödlinger; Bastian Asmus; Martin Fera; Judith Utz; Giorgia Ghiara (PLoS ONE, 2025)
The bronze and brass doors of the 11th and 12th centuries represent the largest group of medieval monumental bronzes still preserved today in Europe. Of the less than 30 doors that have survived, three, the doors of Trani, Ravello and Monreale, were made by Barisanus of Trani. In this work, we present, for the first time, chemical analyses of the metal parts of all the doors and an in-depth study of their production, showing how a detailed observation of the casting characteristics provides information on the chronological order of the doors studied. This paper contributes to the ongoing discussion in art history regarding the chronological order of the construction of the doors. Moreover, the paper demonstrates the potential of scaled orthometric images as a basis for art historical and production-related questions.